Notes on Early Land Plants Today. 17. Transfers of some taxa in Adelanthaceae (Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Herzogobryum teres is the largest member of the genus and differs in many respects morphologically from the rest of the genus. It was included in Herzogobryum Grolle (1964: 160) by Grolle (1966) because of the dorsally interlocked merophytes, a position accepted by Schuster (1996). This character is not constant and cannot be used for generic separation. Morphologically Herzogobryum teres is very similar to Jamesoniella(Spruce 1876: 230) Carrington (1881: 25) species. It has also twice been described under that genus. As Jamesoniella s.str. is now treated within Syzygiella Spruce (1876: 234) we transfer it to the latter genus.